Morphological characteristics of seed starch granules of Fagaceae in South China and their implication in paleodiet - Yu, Tong; Yang, Qing; Deng, Min; Cheng, Nan; Yao, Kaiping; Yang, Wanshu; Ji, Xueping; Zheng, Hongbo (Frontiers in Plant Science, 2022)
Nut fruits likely played a significant role before and during the origin of agriculture; however, relatively little research conducted on the morphological characteristics and statistical comparisons of nut fruit starch granule hinders the progress of paleodietary analysis of prehistorical society. For better species identification of starch granule remaining on tools discovered at archaeological sites, it is desirable to develop a more abundant morphology database of modern nut fruit starch granules as well as the establishment of relevant identification standards. Therefore, nuts from 40 species in four genera (Quercus, Lithocarpus, Castanea, and Castanopsis) of Fagaceae were collected from South China for statistical measurement and comparative analysis. Starch granules are highly accumulated in 34 species except for 6 species, whose shapes involve oval, subcircular, drop-shaped, rounded triangle, polygonal, spherical caps, and bell-shaped types, or a combination of several types, and the average length is between 10 and 20 μm. According to research on Quercus phylogeny relationships, it was found that the species in the same infragenious section produce similar morphological characteristics of starch granules. The result was applied in the identification of starch granules extracted from stone tools from the 20 to 10 ka cultural layer of Xiaodong Rockshelter, and some starch granules can be recognized to species level, revealing that nuts from Quercus and Lithocarpus were gathered and exploited by ancient people. This expansion of modern starch presentation and comparison of nuts helps to improve the accuracy of the identification of ancient starch and deepen the understanding of plant utilization of ancient humans.